RT- PCR testing of upper respiratory tract samples for diagnosis of SARS-CoV-2: Between justification and overestimation, a multi-center international study. Issue 48 (July 2022) - Hammad, Noha M.; Saeed, Maysaa A.; Shaltout, Shaker Wagih; Nofal, Hanaa A.; Nafae, Ramadan M.; Arslan, Kadem; Tanoglu, Alpaslan; Nechifor, Mihai; Luca, Catalina; Al-kadhim, Zaid Hashim Ali; Mosallem, Ahmed; Amer, Fatma A.
Abstract: Background: It has been found that patients recovered from COVID 19 may still test Reverse Transcriptase- Polymerase Chain Reaction (RT- PCR) positive without being infectious; the reasons are unclear. The occurrence of false-negative results of RT- PCR interferes with a proper diagnosis. The objectives of that work were to determine factors associated with persistently detectable SARS-CoV-2 RNA among recovered hospitalized patients and to determine the incidence of false-negative RT-PCR results and associated factors. Methods: Relevant data were collected from 482 COVID 19 patients hospitalized in six referral centers from four countries. Results: The median duration of RT- PCR conversion to negative was 20 days. Out of 482 studied patients, 8.7% tested positive after more than four weeks and were considered prolonged convertors. Binary logistic regression analysis revealed headache as an independent risk factor for short conversion time while fever, hypertension, chronic obstructive pulmonary disease, lymphopenia, elevated erythrocyte sedimentation rate, and the number of lobes affected, and bilateralism were found to be independent risk factors for prolonged positivity. Eighteen patients had initial negative results then turned positive after 24–48 h. Associated factors and outcomes were identified. Conclusion: Identifying patients with a high likelihood of COVID-19 despite a negative RT-PCR is critical for effective clinical care. However, patient isolation resumption depending on positive RT-PCR despite clinical and radiological recovery is an overrating that greatly burdens the health sector.